Space and national security - Stares, Paul B. (Washington, D.C. : The Brookings Institution, 1987)
In this book, the author examines the officially stated rationales for deploying antisatellite weapons and assesses their long-term consequences for U. S. national security. He surveys how the superpowers use space for military purposes and appraises the value of satellites for each side. He also assesses the threats to U. S. and Soviet space systems and the countermeasures that can be employed to reduce their vulnerability. After evaluating the potential usefulness of antisatellite weapons in a range of wartime contingencies, he analyzes the feasibility of arms control in space.
Includes bibliographical references and index.
ne 17/05/2018
Loans
Keywords: Anti-satellite weapons; Astronautics, Military; United States